LED Farbmischung mit chaotischen Lichtleitern - Bonenberger, Theresa (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2016)
This book describes a systematical method to efficiently and homogeneously mix rays of different coloured Light Emitting Diodes (LEDs) in both the angular and spatial domain. The focus of this work is the application of chaotic billiard geometries on the cross section of a light guide. Such a chaotic light guide offers the possibility to achieve complete colour mixing according to deterministic chaos theory.